Shatavarin-IV rescues the Di (2-ethylhexyl) phthalate (DEHP) induced oxidative stress in rat granulosa cells in vitro - Pandey V.; Sharma A.; Tiwari S.; Patel Y.; Chauhan J.K.; Ayesha S.; Sahu A.N.; Gupta R.; Tripathi A.; Dubey P.K. (My University, 2025)
Studies provide notable evidence that oxidative stress (OS) mediated reactive oxygen species (ROS) disturb reproductive health. We have shown in our previous publication that exposure of Di-(2-ethylhexyl) phthalate (DEHP), induces OS mediated ROS generation which inhibits steroid synthesis. In the present study, we demonstrated the ameliorative/protective effects of one of the steroidal saponins, i.e., Shatavarin-IV, isolated from the roots of Asparagus racemosus against DEHP induced OS in rat granulosa cells. Granulosa cells were exposed with DEHP alone (400 μM), Shatavarin-IV alone (8 μg/ml), and a combination of DEHP + Shatavarin-IV (400 μM + 8 μg/ml) in vitro for 24 hrs. Intracellular ROS, OS/hypoxia, mitochondrial membrane potential, steroid-responsive genes expression were analyzed. The results revealed that the effective dose of DEHP (400 µg) significantly increased OS compared to the control by increasing ROS levels, mitochondrial membrane potential, and β-galactosidase activity with a higher level of apoptotic genes (Bax, Caspase-3) expression at mRNA level. Further, DEHP significantly (p < 0.05) reduced mRNA expression of steroidogenic responsive genes (StAR, CYP17A1, and CYP19A1) in granulosa cells treated with above combination compared to control. Interestingly, co-treatment of DEHP + Shatavarin-IV significantly suppressed the DEHP induced OS, ROS, β-galactosidase levels and enhanced steroidogeneic and apoptotic gene expression activities, which suggests that Shatavarin-IV rescued DEHP-induced changes that may useful for the prevention of DEHP- induced reproductive toxicity. © 2024 Elsevier Inc.